PLANT GROWTH-PROMOTING BACTERIA IN THE CONTROL OF FUSARIUM SP - Alves, Afonso Henrique; Dos Santos, Millena Nonato; Moraes, Maryllia Gabriela Botelho; Ferreira, Cleisi Kelly Cruz; Xavier, Lara Juliane Miguel; Marques, Mônica Lau Da Silva; Pessoa, Flávia Oliveira Abrão (Seven Editora, 2026)
The use of plant growth-promoting bacteria (PGPB) has emerged as a sustainable alternative for agricultural management and control of phytopathogens. This study aimed to evaluate the potential of PGPB in controlling Fusarium sp. and promoting plant development. The experiment was conducted in vitro at the Laboratory of Microbial Interactions and Biotechnology (LIMBio/IF Goiano – Campus Ceres), using the bacteria Bacillus amyloliquefaciens, Bacillus subtilis, and Priestia aryabhattai. The antagonism assay was performed by co-inoculation in PDA medium, and the mycelial growth of the fungus was measured to calculate the relative control index. The data were subjected to analysis of variance and Tukey’s test (p < 0.05). All treatments showed a significant effect in controlling the pathogen, with Bacillus amyloliquefaciens standing out, exhibiting the highest antagonism index (69.87%), statistically differing from Bacillus subtilis (31.57%) and Priestia aryabhattai (15.30%). The results indicate that B. amyloliquefaciens has high potential as a biocontrol agent for Fusarium sp., and may contribute to reducing the use of agrochemicals and developing more sustainable agricultural practices.